Perylene derivatives and silicon nanosheets - Haddow, Sarah Louise (2017)
The work presented in this thesis explores two different topics of interest, firstly a synthetic project fabricating small building blocks for supramolecular arrays. The building blocks are a series of perylene monoimide monoahydride (PMIA) compounds, synthesised by a four step process. The PMIA compounds belong to a family of dyes called the rylenes which are known in literature for their optical properties and use in optoelectronic devices. Chapter 2 begins with the description of the synthesis and characterisation of these molecules, where Hirshfeld surface analysis is used to investigate the solid state intermolecular forces between adjacent molecules. This is followed by the details of connecting two PMIA through organic linkers and it explores the structural and physical properties of the so called dimer. The physical properties investigated include, optical and electronic properties utilizing spectroelectrochemistry, cyclic voltammetry and electron paramagnetic resonance techniques. The chapter also explores the asymmetric feature of the building blocks with the aid of X-ray crystallography. The second topic of interest is silicon nanosheets (SiNS). There are many types of these two dimensional (2D) materials published in literature, however one type which has had minimal attention is a buckled sheet structure known as layered polysilane. A synthetic and structural investigation into layered polysilane and closely related siloxene, are carried out in Chapter 3, identifying their bonding arrangement and topographic assembly through a range of analytical techniques. Like many other SiNS, it is proposed that this material can be used in nanotechnology devices in the future, and this thesis makes some way towards identifying the structure which is important in order to use them in such devices. Chapter 4 leads on to discuss the investigation into the modification of SiNS fabricated in Chapter 3, via a range of small organic molecules. This is another area in literature which has great scope for investigation and exciting potential for use in nanodevices. An important difference once the SiNS have been functionalised with small organic groups is their enhanced solubility, in comparison to being insoluble before functionalisation. This opens up a wealth of applications which require solution phase activity. A range of surface analytical techniques aid in identification of functionalised sheets and Chapter 4 details the challenges and successes.